Konsep Ekonomi Jamaah Tabligh: Studi Pemikiran Maulana Muhammad Zakariyya dalam Kitab Fadhilah Al-Tijaarah - Khusniati Rofi'ah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
Jamaah Tabligh is a sect that focuses on the issue of increasing faith and good deeds, by moving to invite and preach through khuruj fiisabilillah, which is going out for 3 days, 40 days or 4 months. Because of the obligation to leave their families for a certain period of time, there is a growing assumption in the community that they often neglect their families during khuruj, do not provide for them and do not work. However, they also have guidelines on economic activities in everyday life, which are contained in the book Fadilah Tijarah by Maulana Zakariyya Al-Kandahlawi. This book not only discusses the virtues of trade, but more broadly discusses how a Muslim should seek the necessities of life by paying attention to the signs of Islamic law. The existence of this book proves that the Tabligh congregation actually also has attention to economic activities and world affairs.